Determinación de la digestibilidad y utilización biológica de proteína dietaria suplementada con acelgas en humanos - Rosales Fernández, Arturo (2003)
To evaluate, in human beings, the effect of dietary suplementation, with the food based on chard leaves (Beta vulgaris L. var. Cicla).The supplement was prepared according to nourishing requirements of pro vitamin A. At the beginning and at the end of the study, it was determined: seric proteins albumins, globulins according to official techniques described by wiener. The digestibility and retained nitrogen, by nitrogen balance technique. The chemical composition of diets and supplement, were applied by AOAC techniques. The results before and then were total seric proteins from 6,68 a 7,29%, albumins: from 3,87 to 4,29%. Protein digestibility from 64 to 66%. The nitrogen retain went up from 3.41 to 5.18 mg/kg of weight/day. The study allows to revalue the nourishing properties and usage of chard as a source of micronutrients for human beings. These changes were significant (p < 0.05).